Pengaruh Kualitas Pelayanan terhadap Kepuasan Masyarakat di Kelurahan Air Dingin Kecamatan Bukitraya Pekanbaru - Mukson, Mukson; Atina Tafano (Lembaga Anotero Scientific, 2021)
The purpose of this study was to determine the effect of service quality on community satisfaction in the Air Cold sub-district, Bukit Raya Pekanbaru. The sample in this study was Air Cold sub-district, Bukit Raya Pekanbaru, which amounted to 100 people. The data analysis used is validity test, reliability test, normality test, heteroscedasticity test, simple linear regression, coefficient of determination test and T test. The influence of service quality on community satisfaction in the Air Cold sub-district, Bukit Raya Pekanbaru district has a significant effect with the coefficient of determination R2 of 0.803. This means that the variable of community satisfaction (Y) is influenced by the service quality variable (X) of 80.3%, while the remaining 19.7% is explained by other factors not examined by the author. The service quality variable (X) has a positive influence on community satisfaction (Y) with a regression coefficient of 0.244 indicating that if the service quality increases by 1 unit, the employee productivity variable will increase by 0.244, which means that the higher the service quality, the higher the community satisfaction. The results of the hypothesis test show the value of tcount > ttable (2,972 > 1,984) with sig 0.000 < sig 0.05, which means Ho is rejected and Ha is accepted. So it can be concluded that the quality of service has a significant effect on community satisfaction in the Air Cold sub-district, Bukit Raya Pekanbaru.